2021
DOI: 10.3390/microorganisms9050901
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Transmission Paths for Three Different Bartonella spp. in Ixodes ricinus Ticks Using Artificial Feeding

Abstract: Bartonellae are facultative intracellular alpha-proteobacteria often transmitted by arthropods. Ixodes ricinus is the most important vector for arthropod-borne pathogens in Europe. However, its vector competence for Bartonella spp. is still unclear. This study aimed to experimentally compare its vector competence for three Bartonella species: B. henselae, B. grahamii, and B. schoenbuchensis. A total of 1333 ticks (1021 nymphs and 312 adults) were separated into four groups, one for each pathogen and a negative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Since then, a number of novel Bartonella strains have been identified from Australia, including novel species described from marsupials and their ectoparasites (ticks and fleas) [118–120]. While generally considered to be transmitted by fleas, reports of Bartonella species isolated from ticks are increasing, as studies take a broader approach to surveillance of vector-associated microbes [65, 121, 122]. Identification of Bartonella in fed ticks does not mean they are a viable vector, but it does highlight that future studies should include ticks when exploring candidate vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a number of novel Bartonella strains have been identified from Australia, including novel species described from marsupials and their ectoparasites (ticks and fleas) [118–120]. While generally considered to be transmitted by fleas, reports of Bartonella species isolated from ticks are increasing, as studies take a broader approach to surveillance of vector-associated microbes [65, 121, 122]. Identification of Bartonella in fed ticks does not mean they are a viable vector, but it does highlight that future studies should include ticks when exploring candidate vectors.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that I. ricinus is a competent vector for both B. henselae and B. birtlesii [19,20]. More recently, B. henselae, B. grahamii, and B. schoenbuchensis DNA were found across the developmental stages of experimentally infected I. ricinus, suggesting more evidence on the potential Bartonella transmission by ticks [21].…”
Section: Introductionmentioning
confidence: 68%
“…The generalist tick I. ricinus , has often been used in studies performed to clarify its competence to transmit the bacteria. The transovarial and transstadial transmission of B. henselae , B. grahamii , and B. schoenbuchensis have been recently demonstrated [ 56 ], while the transmission of B. birtlesii to susceptible mice, using laboratory-infected I. ricinus , was previously achieved [ 57 ]. Rhipicephalus sanguineus being the most prevalent tick in companion animals, has recently been used in similar studies [ 58 , 59 ] but evidence that this tick species can be the vector of Bartonella sp.…”
Section: Discussionmentioning
confidence: 99%